Nanozymes in Tumor Theranostics - Ma, Qiulian; Liu, Yanfang; Zhu, Haitao; Zhang, Lirong; Liao, Xiang (Frontiers in Oncology, 2021)
Nanozymes, a new generation of enzyme mimics, have recently attracted great attention. Nanozymes could catalyze chemical reactions as biological enzymes under physiologically mild conditions with higher-efficiency catalytic activities. Moreover, nanozymes could overcome the shortcomings of natural enzymes, such as easy inactivation, high cost, and low yield. With the development of more and more smart and multi-functional nanosystems, nanozymes display great achievement in tumor biology. In this review, we outline the recent advances of nanozymes in tumor and tumor microenvironment diagnosis, therapy, and theranostics.